PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA LEMBAGA PERBANKAN TAHUN 2014-2018 - Imam Fahri Prio Utomo (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
This study describes the relationship between Good Corporate Governance whit the performance of the company’s finances. The indicator that in the use of Good Corporate Governance is the influencer of independent, commite audit, the board of directors to determine: the influence of Independent ,the influence of the Audit Committee, the board of directore and the influence of the Independent Commissioners and the Audit Committee together the same with the Performance of Banking Companies listed on the Indonesia Stock Exchange in 2014-2018.